Bitter taste receptors in the gut-vascular axis: a novel target for immune and metabolic regulation of hypertension - Wei, Xiaoyu; Lyu, Feifei; Jia, Fuyun; Zhang, Lihong; Zhang, Min; Xu, Qiang; Hua, Shengyu (Frontiers in Immunology, 2026)
Hypertension affects approximately 1.3 billion adults worldwide, yet the control rate remains below 20%, highlighting the limitation of current therapies that primarily lower blood pressure without targeting the underlying pathophysiological mechanisms. Recent research indicates that bitter taste receptors, which are structurally distinct members of the G protein-coupled receptor superfamily, have functions that extend beyond their traditional role in oral taste perception. These receptors are extensively expressed along the gut-vascular axis, including in vascular smooth muscle, cardiac tissue, macrophages, and gastrointestinal organs, thereby positioning them as crucial nodes in the regulation of immunometabolic processes. This review systematically elucidates the complex regulatory mechanisms of gut-vascular axis TAS2Rs in the pathophysiology of hypertension and investigates TAS2R-targeting compounds, with particular emphasis on their effects in modulating blood pressure. This review consolidates evidence on TAS2R signaling across vascular, immune, and gastrointestinal interfaces to outline therapeutic implications for hypertension.